Application of Biophilic Architecture Principles: a Case Study in the Design of Jemursari Hospital, Surabaya - AHMAD DANI PUTRA PRATAMA R. H.; Azkia Avenzoar (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
This study aims to examine the application of biophilic architectural principles in the design of healthcare facilities, specifically at RSI Jemursari Hospital in Surabaya. The background of this research is based on the significant role of the built environment in supporting the healing process of patients, both physically and psychologically. The biophilic design approach is selected as it integrates natural elements into architectural design to enhance spatial quality and user comfort. The research employs a descriptive qualitative method, utilizing literature review and case study analysis as data collection techniques. The study is conducted based on the 14 patterns of biophilic design, which are used as analytical parameters to evaluate architectural elements within the case study object. The results indicate that the implementation of biophilic principles in hospital design improves environmental quality through the optimization of natural lighting, air circulation, the presence of vegetation, and visual connections to nature. These elements contribute to creating a more comfortable environment, reducing patient stress levels, and supporting a more effective healing process. In conclusion, the application of biophilic architecture in hospital design not only serves an aesthetic function but also plays a significant role in enhancing the health and well-being of building users.